TAFSIRWEB: DIGITALIZATION OF QUR'ANIC INTERPRETATION AND DEMOCRATIZATION OF RELIGIOUS SOURCES IN INDONESIA - Achmad Rifai (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
TThe presence of the internet as a sign of the emergence of new media also creates a new medium in the interpretation of the al-Qur’an. This phenomenon is interesting to examine in order to complement the study of the interpretation of the al-Qur’an that existed before its appearance in new media. In examining this topic, which is related to the interpretation of the al-Qur’an on the tafsirweb.com website, the author uses a textual method by adopting a content analysis model. There are two things that are the results of this research, namely the digitization of interpretation to become the central spirit in tafsirweb.com, and the translation of tafsir books that leads to the democratization of religious sources. This is the contribution of this determination to fill in the gaps that scholars have neglected in examining the interpretation of the al-Qur’an.